(untitled) (Menara Perkebunan, 2025)
Basal stem rot (BSR) is a major disease of oil palm. One approach to control the pathogen is by using organic fungicides. This study aims to assess the efficacy of two kinds of fungicides, organosulfur and polyphenol, in suppressing Ganoderma boninense and their impact on seedlings. Poisoned agar media were used in the in vitro assay with organosulfur at concentrations of 0.8% and 0.125%, polyphenol at 1.6% and 0.125%, and two combinations: 0.8% organosulfur + 0.125% polyphenol and 1.6% organosulfur + 0.125% polyphenol (v/v), with a 3-replication test. In vivo trials were conducted on 4-month-old oil palm seedlings inoculated with G. boninense. Two treatments were tested: Combination 1 (0.8% organosulfur + 0.125% polyphenol, v/v) and Combination 2 (1.6% organosulfur + 0.125% polyphenol, v/v). The solution was applied by soil drenching, 200 mL per plant, at the stem base every 14 days, totalling four applications within a 3-month period. The treatments were evaluated under three levels of disease severity: Group 1 (asymptomatic plants with fungal fruiting bodies), Group 2 (leaf necrosis ≤ 50%), and Group 3 (leaf necrosis ≥ 50%). The first result demonstrated a full inhibition of fungal growth in treatments with 1.6% polyphenol and the combination of 1.6% organosulfur + 0.125% polyphenol (v/v). In vivo assay results showed that an increase in resistance (measured by prolonged survival) was observed in Groups 1 and 2. These findings indicate that combining organosulfur and polyphenol fungicides can improve seedling resistance to BSR, particularly at early and moderate disease stages.